Inclusive Leadership and Emotional Intelligence: Strategies to Address Grapevine Communication in Private HEIs - Dr. Mehtab Begum Siddiqui; Dr. Maria Shaikh; Dr. Erum Shah; Usayd Jamil Qureshi (Research Journal of Psychology, 2025)
The study investigates how leaders’ emotional intelligence reduces negative workplace communication flows at private universities located in Sindh province, Pakistan. This study investigates the moderating impact of inclusive leadership style among these findings. The research gathered data from 243 participants through snowball sampling before measuring these results on a 5-point Likert-type scale. The research team used Structural Equation Modeling with Smart PLS to examine the proposed model relationships. Results show that leaders with emotional intelligence display lower grapevine communication which becomes more pronounced when they demonstrate an inclusive style of leadership. The study brings important findings which help higher education institutions use emotional intelligence and inclusive leadership practices to develop cohesive and productive workplaces.